Disability and quality of life in patients with fibromyalgia - Verbunt, Jeanine A (BioMed Central, 2008)
BACKGROUND: Patients with fibromyalgia often feel disabled in the performance of daily activities. Psychological factors seem to play a pronounced disabling role in fibromyalgia. The objectives of the study are: Firstly, to investigate contributing factors for disability in fibromyalgia. Secondly, to study psychological distress in patients with fibromyalgia as compared to other nonspecific pain syndromes. And finally, to explore the impact of fibromyalgia on a patient's quality of life. METHODS: In this cross sectional study, explaining factors for disability were studied based on a regression analysis with gender, mental health, physical and social functioning as independent variables. For the assessment of disability in fibromyalgia the FIQ was used. The levels of psychological distress in patients with fibromyalgia, Complex Regional Pain Syndrome (CRPS) and chronic low back pain (CLBP) were compared based on scores on the Symptom Checklist (SCL90). Quality of life of patients with fibromyalgia was compared with scores (SF36) of both patients with fibromyalgia and other health conditions as derived from the literature. RESULTS: Disability in fibromyalgia seemed best explained by a patients mental health condition (β = -0.360 p = 0.02). The level of psychological distress was higher in patients with fibromyalgia as compared to patients with CRPS or CLBP (p < 0.01). The impact of fibromyalgia on quality of life appeared to be high as compared to the impact of other health conditions. CONCLUSION: Patients with fibromyalgia report a considerable impact on their quality of life and their perceived disability level seems influenced by their mental health condition. In comparison with patients with other pain conditions psychological distress is higher.